Proof of Golomb’s conjecture in Fq with Γ$-pseudorandom sequences (European Journal of Pure and Applied Mathematics, 2020)
This article offers a short proof of Golomb's conjecture, and then our results show that the sequences are pseudorandom in $\mathbb{F}_2$.
Keywords: Primes; Primitive roots; Finite fields; Sequences; Golomb's conjecture